Kaszópusztai vadászatok : 1912-1926 - Kaposi, Zoltán (Közép-Európai Közlemények, 2016)
Kaszópuszta is a small village in the western part of Somogy County. The local hunting ground was created by Christian Kraft zu Hohenlohe-Öhringen, a wealthy German prince famous for his passion for hunting. Before that the area belonged to the village of Somogyszob and it was acquired by the prince in 1912 from the Cathedral Chapter of Esztergom. He enhanced the estate with further land purchases which ended up in a 115 km2 area. The game preserve in Kaszó was made along the lines of his other land the Javorina Estate in the High Tatras. His hunting lodge was built of larch brought from Silesia. He developed public infrastructure including electricity, water supply and roads on his estate. He managed his estate in Prussian spirit. The prince, who was one of the wealthiest man of Germany also possessed huge industrial corporations, arranged world famous hunts in Kaszó where princes and emperors (including members of the Habsburg and the Hohenzollern families) were also present. The prince died in 1926 and his heirs paid less attention to the estate in Kaszó.